Revealing Interactions between Temperature and Salinity and Their Effects on the Growth of Freshwater Diatoms by Empirical Modelling - T. T. Yen Le; Alina Becker; Jana Kleinschmidt; Ntambwe Albert Serge Mayombo; Luan Farias; Sára Beszteri; Bánk Beszteri (Phycology, 2023)
Salinization and warming are of increasing concern for freshwater ecosystems. Interactive effects of stressors are often studied in bifactorial, two-level experimental setups. The shape of environmental reaction norms and the position of the “control” conditions along them, however, can influence the sign and magnitude of individual responses as well as interactive effects. We empirically model binary-stressor effects in the form of three-dimensional reaction norm surfaces. We monitored the growth of clonal cultures of six freshwater diatoms, Cymbella cf. incurvata, Nitzschia linearis, Cyclotella meneghiniana, Melosira varians, Ulnaria acus, and Navicula gregaria at various temperature (up to 28 °C) and salinity (until the growth ceased) shock treatments. Fitting a broad range of models and comparing them using the Akaike information criterion revealed a large heterogeneity of effects. A bell-shaped curve was often observed in the response of the diatoms to temperature changes, while their growth tended to decrease with increasing electrical conductivity. C. meneghiniana was more tolerant to temperature, whilst C. incurvata and C. meneghiniana were the most sensitive to salinity changes. Empirical modelling revealed interactive effects of temperature and salinity on the slope and the breadth of response curves. Contrasting types of interactions indicates uncertainties in the estimation by empirical modelling.